Business Process Reengineering in public sector - Vacek, Antonín; Řepa, Václav, 1958-; Hrabě, Pavel; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2011)
The main goal of this work is to create some kind of simple methodology that can help to improve effectiveness of public organizations. There're a lot of theories and methodologies focused on this topic and there is a good chance many new ones will be presented in the future. These came mainly from management field and sometimes from other fields as well. This work focuses mainly on Business Process Reengineering and combines it with other methodologies hoping, it will help in a process improvements in the public sector. Focus is on Czech Republic but this work should be useful to other countries as well, if necessary changes are made in order to shape things that are different between the countries. In this work, a whole project cycle of the public organization processes improvement project can be found, but some project phases will be explained in more detail then the other. Focus is on the analytic parts of the project (strategy creation, use of UML, BSC and other models and methodologies like that) rather than the project management parts of the project. All the practical examples are from public sector organization -- namely the administrative office of one of the city districts of Prague. After reading this work, reader should have moderate understanding of the application of a BPR methodology in the public sector and how it can be supported by other methodologies. There is also big portion of models and diagrams in this work showing pieces of reality from chosen public organization. Their meaning is to show what is usually done in this kind of project and how to understand the models. This works goal isn't creation of a guideline to UML or any other modeling principles.
Vedoucí práce: Václav Řepa
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2011
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2011
Způsob přístupu: Internet
Keywords: informační systémy a technologie [obor dipl. práce]; diplomové práce; master's theses